A self-suspending proppant for low-water fracturing
By adsorbing tetramers on the surface of self-suspended proppant, the lack of performance under high mineralization and low temperature conditions is solved, and higher salt resistance and low temperature rubber breaking capabilities are achieved, and it is suitable for fracturing processes under high salt and low temperature conditions.
Patent Information
- Application Number
- CN202411860844.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing self-suspended proppants have poor suspension performance in solutions with high mineralization and insufficient low-temperature glue breaking ability, making it difficult to meet the fracturing needs under high salt and low-temperature conditions.
By regulating the polymerization unit of the expansion resin, the salt resistance and low-temperature rubber breaking performance of the self-suspended proppant are improved, so that it can maintain good performance under high mineralization and low-temperature conditions.
The suspension performance and low-temperature rubber breaking ability of self-suspended proppants in high-mineralization solutions are significantly improved, and the use of conventional water and high-mineralization reflux and sewage can be used, and the water saving and reflux efficiency of the fracturing process is improved.
Smart Images

Figure CN119307250B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drilling compositions, and in particular to a self-suspending proppant for low-water fracturing. Background Art
[0002] Since modern low-water fracturing technology adopts a large-scale transformation model, a single well needs 30,000 to 50,000 cubic meters of water, which has high requirements for water resources. At the same time, the water-scarce areas in Shanxi and northern Shaanxi have even higher requirements for water resources. The lack of water resources often affects the progress of oil and gas field development. On the other hand, the large increase in water consumption in engineering projects has a great impact on the local ecology and causes great pollution. Therefore, the technical demand for low-water fracturing has gradually been proposed. Low-water fracturing technology is aimed at conventional hydraulic fracturing technology. It means that under the premise of completing the same geometric size of fractures (including single main fractures turning into branch fractures and micro fractures, etc.) and transporting and laying the same volume of proppants with the same particle size, the water consumption of fracturing operations can be reduced to varying degrees.
[0003] Conventional carbon dioxide or nitrogen foam fracturing technology can also reduce water consumption to varying degrees, such as foam quality can reach 30%~70%, up to more than 95%. However, the foam fracturing fluid has high viscosity and strong Jamin effect, which makes it difficult to communicate and extend small and micro-scale fracture systems. It can often only form a single main fracture and cannot meet the process requirements for forming complex fractures. In addition, the conventional foam fracturing fluid has high friction and low static liquid column pressure, which leads to high wellhead pump pressure during fracturing operations and limited construction displacement, thereby reducing the final sand addition amount. Carbon dioxide dry fracturing utilizes the ultra-low viscosity of supercritical carbon dioxide, which can communicate and extend small and micro-scale fracture systems, but because its viscosity is too low, the amount of sand added and the sand-to-liquid ratio are relatively low. Even if carbon dioxide thickening technology is used, it still cannot meet the process requirements of strong sand addition. In addition, a fatal flaw of waterless fracturing technologies such as carbon dioxide fracturing is the lack of a hydration mechanism, which plays an indispensable role in lowering the compressive strength and fracture pressure of rocks, connecting and extending small and micro-scale fracture systems, increasing the porosity and permeability of the rock matrix near the fractures, and improving the post-fracturing imbibition effect.
[0004] Self-suspended proppants can greatly reduce the water consumption of single well fracturing, and the water reduction ratio exceeds 50%, which can meet the requirements of modern fracturing for less water. The principle is: self-suspended proppants are coated with a layer of functional additives on the surface of conventional proppant aggregates (including quartz sand, ceramsite, etc.), so that the self-suspended proppants can quickly hydrate and swell after encountering water, forming a layer of hydrogel on its surface, reducing its own relative density, while increasing the viscosity and viscoelasticity of water, so that the self-suspended proppants can be in a suspended state, and can be well suspended and evenly distributed in the fracturing fluid. With the hydraulic fracturing fluid, the self-suspended proppants can effectively transport the proppants without sedimentation and stratification. Traditional debonding agents can be used to break the gel and release the proppant after it is transported to the designated location. At the same time, the sand ratio of the sand mixing fluid can be greatly increased, thereby achieving the effect of greatly reducing the water consumption.
[0005] On September 25, 2017, Zhang Xin et al. disclosed an expandable self-suspending proppant in the article "Preparation and Performance Evaluation of Expandable Self-Suspending Proppant". The proppant treated with comonomers (acrylamide (AM), acrylic acid (AA), N, N'-methylenebisacrylamide (MBA), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), with a mass ratio of 71:40:1:8) and a silane coupling agent (KH570) was polymerized under the action of an initiator, double bonds were introduced by silane coupling modification on the proppant surface, and the expandable resin was grafted on the proppant surface through a graft polymerization reaction. The expansion multiple of the obtained self-suspending proppant in clean water was 1.5~5. The fracturing simulation results showed that the migration and laying effect of the self-suspending proppant was better than that of the conventional proppant. The half-length of the supported fracture was 119.2 m, which was 24% higher than that of the conventional proppant.
[0006] However, the above-mentioned expandable self-suspending proppant can only use clean water with low mineralization, such as purified water, and has no salt resistance. If the mineralization is slightly higher, the suspension performance will deteriorate, and the low-temperature debonding ability is poor. Summary of the invention
[0007] The invention provides a self-suspending proppant for low-water fracturing, which solves the problems of poor salt resistance and low-temperature gel breaking ability of the existing self-suspending proppant.
[0008] In order to solve the above technical problems, the technical solution of the self-suspending proppant for low-water fracturing of the present invention is:
[0009] A self-suspending proppant for low-water fracturing, comprising a modified proppant and a quaternary copolymer adsorbed on the surface of the modified proppant; the modified proppant is obtained by surface-modifying the proppant with a modifier, the modifier being a silane coupling agent and / or a nonionic surfactant; the comonomers of the quaternary copolymer are acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyltrimethylammonium chloride and acrylic acid, respectively.
[0010] The present invention is an improvement on the prior art, and provides a self-suspending proppant for water-poor fracturing. By adopting four copolymer monomers of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyl trimethyl ammonium chloride and acrylic acid to form a tetrapolymer, the salt resistance of the self-suspending proppant can be greatly improved, and good suspension performance can still be maintained in a solution with a high mineralization degree, so that the self-suspending proppant provided by the present invention has low requirements on water quality, and can not only use conventional river water and surface water, but also can use oil field backflow fluid and treated sewage, which further highlights the water-saving function of the self-suspending proppant of the present invention. In addition, the tetrapolymer has good low-temperature gel breaking performance, and adopts traditional persulfate gel breakers to destroy the chain structure of the copolymer at 50°C, reduce the viscosity of the system, and the adsorption of the tetrapolymer on the surface of the modified proppant can release the proppant more quickly, and the backflow efficiency is high. Compared with high-temperature gel breaking, the operation is simpler and the cost is lower.
[0011] In order to further improve the salt resistance of the self-suspending proppant, preferably, the mass ratio of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyltrimethylammonium chloride and acrylic acid is (1~1.55):(0.03~0.07):(1~1.22):(1~1.18).
[0012] In order to further simplify the preparation of the self-suspending proppant, preferably, the self-suspending proppant is obtained by impregnating the modified proppant in a tetrapolymer solution and then drying the solution, wherein the tetrapolymer solution comprises 30-50% by mass of the tetrapolymer.
[0013] In order to further improve the impregnation efficiency of the tetrapolymer, preferably, the tetrapolymer solution is composed of the following components by mass fraction: 30-50% of the tetrapolymer, 2-8% of sodium bicarbonate, 1-3% of polyethylene glycol, 1-3% of a defoamer and water. Sodium bicarbonate is used to adjust the pH of the tetrapolymer solution to make the dispersion of the tetrapolymer more stable; polyethylene glycol is used to increase the dispersion solubility of the tetrapolymer; and the defoamer is used to eliminate the foam of the tetrapolymer solution.
[0014] In order to further improve the suspension ability of the self-suspending proppant in a solution with a higher mineralization degree, preferably, the mass ratio of the modified proppant to the tetrapolymer solution is (10-12): (88-90).
[0015] In order to further improve the adsorption of the tetrapolymer on the proppant surface, preferably, the temperature during the immersion treatment and drying is 40-55° C., the immersion treatment time is 120-240 minutes, and the drying time is 4-6 hours.
[0016] In order to further increase the degree of polymerization of the quadripolymer and reduce the energy required for the initiation of copolymerization of the quadripolymer, preferably, the quadripolymer is obtained by polymerizing the comonomer in a solvent under the action of an initiator, the comonomer accounts for 25-32% of the total mass of the reaction system formed by the comonomer, the initiator and the solvent, and the amount of the initiator added is 0.05-0.15% of the total mass of the reaction system.
[0017] In order to further improve the polymerization efficiency, preferably, the polymerization reaction temperature is 40-60° C., the polymerization reaction time is 6-8 h, and the system pH during the polymerization reaction is 8-9.
[0018] In order to further improve the adsorption effect between the proppant and the quadripolymer, preferably, the modifier is a silane coupling agent and a non-ionic surfactant in a mass ratio of (1-5): (2-5), the silane coupling agent is γ-aminopropyltriethoxysilane, and the non-ionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, alkyl alcohol amide, and alkylphenol polyoxyethylene ether.
[0019] In order to further improve the adsorption of the tetrapolymer on the proppant surface, preferably, the surface modification is to immerse the proppant in a modifier solution for 30 to 60 minutes, and the modifier solution includes a modifier with a mass fraction of 3 to 18%. In order to further improve the adsorption of the tetrapolymer on the proppant surface, preferably, the mass ratio of the proppant to the modifier solution is (2 to 3.5): (96.5 to 98). BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The test results of viscosity and suspension time of self-suspending proppant in brines with different salinity;
[0021] Figure 2 The figure shows the test results of low temperature debonding performance of self-suspended proppant. DETAILED DESCRIPTION
[0022] The technical concept of the self-suspending proppant for low-water fracturing of the present invention is as follows:
[0023] Existing fracturing technology generally adopts the mode of slick water + proppant. Since slick water itself has a weak ability to suspend sand, the proppant will settle quickly. Therefore, the maximum sand ratio is generally 26%. If the sand ratio is increased further, there is a risk of sand blockage. The undesirable effect is: the water consumption is huge, about 30,000 to 50,000 cubic meters for a single well. At the same time, in the mode of slick water + proppant, since the sand-carrying fluid will settle after entering the crack, the result is that the proppant only forms effective support at the bottom of the crack, and the crack will close quickly because there is no proppant in the upper part of the crack. The closed crack does not have the function of providing conductivity, so it will affect the long-term conductivity of the crack, and ultimately lead to poor production increase effect.
[0024] The existing technology uses self-suspending proppants to reduce the water consumption of single well fracturing. The self-suspending proppants are obtained by grafting swelling resins (polymer monomers are AM, AA, MBA, and AMPS) on the proppant surface. However, the self-suspending proppants have poor suspension performance in fracturing fluids with high mineralization and poor low-temperature gel breaking ability. The present invention improves the salt tolerance of the self-suspending proppants by regulating the polymer units of the swelling resin, so that the fracturing fluid can use conventional water, backflow fluid, treated sewage and other high-mineralization water, which is beneficial to water saving and less water in the fracturing process. The adsorption of the quaternary polymer and the proppant is combined to improve the low-temperature gel breaking ability and proppant release efficiency, thereby improving the backflow efficiency.
[0025] The method for preparing a self-suspending proppant for low-water fracturing provided by the present invention comprises the following steps:
[0026] (1) Surface modification: The proppant is immersed in a modifier solution for 5-10 min for surface modification to obtain a modified proppant. The mass ratio of the proppant to the modifier solution is (2-3.5):(96.5-98). The modifier solution is composed of 1-8% silane coupling agent, 2-10% non-ionic surfactant, 35-40% ethanol or methanol and the balance water.
[0027] (2) Preparation of tetrapolymer: Four copolymers of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyl trimethyl ammonium chloride and acrylic acid in a mass ratio of (1-1.55): (0.03-0.07): (1-1.22): (1-1.18) are polymerized in water under the action of an initiator and a crosslinking agent to obtain a tetrapolymer. The copolymer, water, initiator and crosslinking agent form a reaction system, wherein the copolymer, initiator and crosslinking agent account for 18-32%, 0.05-0.15% and 0.5-1% of the total mass of the reaction system, respectively. The polymerization temperature is 30-60°C, the polymerization time is 4-8h, and the system pH during the polymerization reaction is 8-10. It is understood that an inhibitor can also be added during the polymerization reaction to control the reaction rate, and the inhibitor is sodium bisulfite.
[0028] (3) Preparation of a self-suspending proppant: The modified proppant obtained in step (1) is added to a tetrapolymer solution at 40-55° C. and immersed for 120-360 min, and then dried at 40-55° C. for 4-6 h to obtain a self-suspending proppant. The mass ratio of the modified proppant to the tetrapolymer solution is (3-12):(88-97). The tetrapolymer solution is composed of the following components in mass fractions: 30-50% of the tetrapolymer, 2-8% of sodium bicarbonate, 1-3% of polyethylene glycol, 1-3% of a defoaming agent and water.
[0029] In a specific embodiment, the proppant surface is cleaned in a methanol or ethanol aqueous solution with a mass fraction of 10-25% before the modification treatment to remove impurities on the proppant surface.
[0030] In a specific implementation manner, the system is in a stirring state during the surface modification in step (1), and is dried at 50-65° C. after the surface modification is completed.
[0031] In a specific embodiment, the tetrapolymer obtained in step (2) is a hydrophobic associating polymer with a molecular weight of 8 to 21 million.
[0032] In a specific embodiment, the initiator in step (2) is one or both of ammonium persulfate and azobisisobutyronitrile; and the cross-linking agent is N,N'-methylenebisacrylamide.
[0033] In a specific embodiment, the pH of the system during the polymerization reaction in step (2) is adjusted by sodium bicarbonate or sodium hydroxide.
[0034] In a specific embodiment, the tetrapolymer obtained in step (2) is dried, ground, and sieved to obtain a polymer powder, and the particle size of the polymer powder is greater than 160-200 mesh. The grinding and sieving need to be carried out in a dry environment and cannot come into contact with water.
[0035] In a specific embodiment, the polyethylene glycol in step (3) is selected from one of polyethylene glycol 200, polyethylene glycol 400 and polyethylene glycol 600.
[0036] In a specific embodiment, the defoaming agent in step (3) is methyl silicone oil.
[0037] The embodiments of the present invention are further described below in conjunction with specific examples. The chemical reagents involved in the following examples are all commercially available conventional products unless otherwise specified.
[0038] 1. Specific embodiments of the self-suspending proppant for low-water fracturing of the present invention
[0039] Example 1
[0040] The self-suspending proppant for low-water fracturing in this embodiment is composed of a modified proppant and a quaternary copolymer adsorbed on the surface of the modified proppant. The modified proppant is obtained by surface modification of the proppant by a modifier formed by a silane coupling agent KH550 (γ-aminopropyltriethoxysilane) and an alkylphenol polyoxyethylene ether. The comonomers of the quaternary copolymer are acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyltrimethylammonium chloride and acrylic acid in a mass ratio of 1:0.05:1:1.1, respectively. The molecular weight of the quaternary copolymer is 8 to 21 million.
[0041] The preparation method of the self-suspending proppant for low-water fracturing in this embodiment is as follows:
[0042] (1) Cleaning: The proppant was cleaned in a 20% by mass methanol aqueous solution to remove impurities on the proppant surface, and then dried at 50°C for later use.
[0043] (2) Surface modification: The proppant cleaned in step (1) was immersed in a modifier solution for 30 min for surface modification. During the surface modification, the system was in a stirring state to obtain a modified proppant. The mass ratio of the proppant to the modifier solution was 3:97. The modifier solution consisted of 5% silane coupling agent KH550, 5% nonionic surfactant alkylphenol polyoxyethylene ether, 35% ethanol and the balance water. After the surface modification was completed, the proppant was vacuum dried at 50°C.
[0044] (3) Preparation of tetrapolymer: Four copolymers of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyltrimethylammonium chloride and acrylic acid in a mass ratio of 1:0.05:1:1.1 were polymerized in water under the action of initiator ammonium persulfate and cross-linking agent N,N'-methylenebisacrylamide to obtain a tetrapolymer. The copolymer, water, initiator and cross-linking agent formed a reaction system, wherein the copolymer, initiator ammonium persulfate and cross-linking agent N,N'-methylenebisacrylamide accounted for 27%, 0.1% and 0.5% of the total mass of the reaction system, respectively. The polymerization temperature was 50°C and the polymerization time was 7 h. The pH of the system during the polymerization reaction was adjusted to pH=8 by sodium bicarbonate. The polymerization reaction was kept stirring at a speed of 50 rpm. The molecular weight of the obtained tetrapolymer was 8 to 21 million. The polymer powder was obtained after drying, grinding and sieving through a 200 mesh sieve.
[0045] (4) Preparation of self-suspending proppant: The modified proppant obtained in step (2) is added to the tetrapolymer solution at 50° C. and immersed in a stirring state for 120 min, then dried at 50° C. for 6 h, and cooled to obtain a self-suspending proppant, wherein the mass ratio of the modified proppant to the tetrapolymer solution is 10:90, and the tetrapolymer solution is composed of 40% of the tetrapolymer obtained in step (3), 5% of sodium bicarbonate, 2% of polyethylene glycol 200, 2% of defoaming agent methyl silicone oil and the balance of water.
[0046] Example 2
[0047] The self-suspending proppant for low-water fracturing in this embodiment is composed of a modified proppant and a quaternary copolymer adsorbed on the surface of the modified proppant. The modified proppant is obtained by surface modification of the proppant by a modifier formed by a silane coupling agent KH550 (γ-aminopropyltriethoxysilane) and an alkylphenol polyoxyethylene ether. The comonomers of the quaternary copolymer are acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyltrimethylammonium chloride and acrylic acid in a mass ratio of 1.1:0.04:1.1:1.18, respectively. The molecular weight of the quaternary copolymer is 8 to 21 million.
[0048] The preparation method of the self-suspending proppant for low-water fracturing in this embodiment is as follows:
[0049] (1) Cleaning: The proppant was cleaned in a 20% by mass methanol aqueous solution to remove impurities on the proppant surface, and then dried at 50°C for later use.
[0050] (2) Surface modification: The proppant cleaned in step (1) was immersed in a modifier solution for 60 min for surface modification. During the surface modification, the system was in a stirring state to obtain a modified proppant. The mass ratio of the proppant to the modifier solution was 3:97. The modifier solution consisted of 5% silane coupling agent KH550, 5% non-ionic surfactant alkylphenol polyoxyethylene ether, 35% methanol and the balance water. After the surface modification was completed, the proppant was vacuum dried at 50°C.
[0051] (3) Preparation of tetrapolymer: Four copolymers of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyltrimethylammonium chloride and acrylic acid in a mass ratio of 1.1:0.04:1.1:1.18 were polymerized in water under the action of initiator azobisisobutyronitrile and cross-linking agent N,N'-methylenebisacrylamide to obtain a tetrapolymer. The copolymer, water, initiator and cross-linking agent formed a reaction system, wherein the copolymer, initiator azobisisobutyronitrile and cross-linking agent N,N'-methylenebisacrylamide accounted for 30%, 0.1% and 0.5% of the total mass of the reaction system, respectively. The polymerization temperature was 50°C and the polymerization time was 7 h. The pH of the system during the polymerization reaction was adjusted to pH=8 by sodium bicarbonate. The polymerization reaction was kept stirring at a speed of 50 rpm. The molecular weight of the obtained tetrapolymer was 8 to 21 million. The polymer powder was obtained after drying, grinding and sieving through a 200 mesh sieve.
[0052] (4) Preparation of self-suspending proppant: The modified proppant obtained in step (2) is added to the tetrapolymer solution at 50° C. and immersed in a stirring state for 240 min, then dried at 50° C. for 6 h, and cooled to obtain a self-suspending proppant, wherein the mass ratio of the modified proppant to the tetrapolymer solution is 10:90, and the tetrapolymer solution is composed of 50% of the tetrapolymer obtained in step (3), 5% of sodium bicarbonate, 2% of polyethylene glycol 200, 2% of defoaming agent methyl silicone oil, and the balance of water.
[0053] 2. Comparison
[0054] Comparative Example 1
[0055] The self-suspending proppant of this comparative example is prepared by the following method:
[0056] (1) Cleaning: Rinse the proppant three times with distilled water and organic solvent ethanol respectively to remove organic and inorganic impurities on the surface of the proppant.
[0057] (2) Surface modification: The proppant obtained by washing in step (1) was immersed in a silane coupling agent solution (KH570, mass concentration 1%) for 24 h, and then vacuum dried at 50° C. to obtain a modified proppant.
[0058] (3) Preparation of self-suspending proppant: Comonomers (acrylic acid AA, acrylamide AM, 2-acrylamido-2-methylpropanesulfonic acid AMPS, N,N'-methylenebisacrylamide BIS) and the modified proppant obtained in step (2) were added into a three-necked flask, the mass ratio of modified proppant, AM, AA, BIS, and AMPS being 620:48:41:3:8, 1% of the total mass of the initiator 2'2-azo[2-(2-imidazoline-2-generation)propane] dihydrochloride was added, and 30% by mass of sodium hydroxide solution was added. The three-necked flask was placed in a constant temperature water bath at 30°C, nitrogen was passed through for 30 min, and the mixture was stirred evenly. After standing for 6 h to react, the polymer was taken out and dried in a drying oven at 80°C to constant weight, and sieved to obtain a self-suspending proppant.
[0059] 3. Experimental Examples
[0060] Experimental Example 1
[0061] This experimental example tests the salt resistance of the self-suspending proppant of the embodiment and the comparative example. Specifically, 10g of the self-suspending proppant is added to 90g of saline with a salinity of 50000ppm (5% KCl solution) and salinity of 70000ppm (7% KCl solution), respectively. Stirring is stopped after 15s, and the solution is left to stand for 1min. The apparent viscosity of the solution is tested using a six-speed rotary viscometer. The suspension time of the self-suspending proppant is recorded. The time when the sedimentation ratio of the self-suspending proppant exceeds 10% is recorded as the suspension time of the self-suspending proppant. The test results are as follows: Figure 1 shown.
[0062] from Figure 1 It can be seen that in 50000ppm and 70000ppm saline water with a mineralization degree, the viscosity of the self-suspending proppant provided by the present invention is much higher than that of Comparative Example 1, and the suspension time of the self-suspending proppant is more than 20 times that of Comparative Example 1. The suspension performance of the self-suspending proppant provided by the present invention in saline water is significantly better than that of Comparative Example 1.
[0063] Experimental Example 2
[0064] In this experimental example, the low-temperature debonding performance of the self-suspending proppant of the embodiment and the comparative example is tested. Specifically, the self-suspending proppant is added to 50000 ppm of brine (5% KCl solution), stirred for 15 seconds, then stopped stirring, and allowed to stand for 1 minute to fully suspend in the brine, and then 0.05% of the debonding agent ammonium persulfate is added. After stirring for 1 hour at 50°C, the apparent viscosity of the solution is tested using an Ubbelohde viscometer. The test results are as follows: Figure 2 shown.
[0065] from Figure 2It can be seen that under the same degelling conditions, the viscosity of the self-suspending proppant solution provided by the present invention drops to 1 mpa·s, while the viscosity of the self-suspending proppant solution of Comparative Example 1 is much higher than that of the present invention, indicating that the low-temperature degelling performance of the self-suspending proppant provided by the present invention is better than that of Comparative Example 1.
[0066] Experimental Example 3
[0067] This experimental example is to apply the embodiment and conventional proppants to a low-water fracturing process of a deep coalbed methane in the Jinxi flexural belt (Shanxi region) in the northeast of the Ordos Basin to solve the problem of water shortage in the region, and at the same time give play to the effect of the self-suspending proppant of the present invention in uniformly spreading sand in the formation fracturing cracks, so as to achieve the ultimate purpose of improving the fracture conductivity and increasing the coalbed methane production. Table 1 shows the process parameters and application results of the self-suspending proppant applied to the low-water fracturing process.
[0068] Table 1 Process parameters and application results of self-suspending proppant in low-water fracturing process
[0069] Add sand amount Water consumption Water reduction rate Production after fracturing Yield increase Example 1 300 square meters 1215 square meters 51.36% About 6000m3 / day About 100% Example 2 250 square meters 1123 square 41.33% About 7200m3 / day About 140% Conventional proppant 300 square meters 2498 square meters / About 3000m3 / day
[0070] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A self-suspending proppant for low-water fracturing, characterized in that: The self-suspending proppant comprises a modified proppant and a quaternary copolymer adsorbed on the surface of the modified proppant; the modified proppant is obtained by surface-modifying the proppant with a modifier, wherein the modifier is a silane coupling agent and a nonionic surfactant; the comonomers of the quaternary copolymer are respectively acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyl trimethylammonium chloride and acrylic acid; the nonionic surfactant is an alkylphenol polyoxyethylene ether; the self-suspending proppant is obtained by immersing the modified proppant in a quaternary copolymer solution. The modified proppant is treated and dried to obtain a polyol; the mass ratio of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, 2-methacryloyloxyethyl trimethyl ammonium chloride and acrylic acid is (1-1.55): (0.03-0.07): (1-1.22): (1-1.18); the mass ratio of the modified proppant and the quaternary copolymer solution is (10-12): (88-90); the modifier is a silane coupling agent and a nonionic surfactant in a mass ratio of (1-5): (2-5), and the silane coupling agent is γ-aminopropyl triethoxysilane; The surface modification is performed by immersing the proppant in a modifier solution for 30 to 60 minutes, wherein the modifier solution includes a modifier with a mass fraction of 3 to 18%.
2. The self-suspending proppant for low-water fracturing according to claim 1, characterized in that: The tetrapolymer solution includes 30-50% by mass of the tetrapolymer.
3. The self-suspending proppant for low-water fracturing according to claim 2, characterized in that: The tetrapolymer solution consists of the following components in mass fractions: 30-50% of the tetrapolymer, 2-8% of sodium bicarbonate, 1-3% of polyethylene glycol, 1-3% of a defoaming agent and water.
4. The self-suspending proppant for low-water fracturing according to claim 2, characterized in that: The temperature during the dipping and drying is 40-55°C, the dipping time is 120-240 minutes, and the drying time is 4-6 hours.
5. The self-suspending proppant for low-water fracturing according to any one of claims 1 to 4, characterized in that: The quaternary copolymer is obtained by polymerizing a comonomer in a solvent under the action of an initiator, wherein the comonomer accounts for 25-32% of the total mass of the reaction system formed by the comonomer, the initiator and the solvent, and the amount of the initiator added is 0.05-0.15% of the total mass of the reaction system.
6. The self-suspending proppant for low-water fracturing according to claim 5, characterized in that: The polymerization reaction temperature is 40~60°C, the polymerization reaction time is 6~8h, and the system pH during the polymerization reaction is 8~9.
Citation Information
Patent Citations
Synthetic method of salt tolerant quadripolymer superabsorbent resin
CN102351976A
Preparation method for self-suspension propping agent in laboratory
CN106634939A